P208 Differentiating intestinal tuberculosis from Crohn's Disease: External validation of a new nomogram. (27th May 2021) - Dahmani, W; Sahar, N; Ay, H; Nour, E; Wafa, B A; Aida, B S; Ahlem, B; Mehdi, K; Hanene, J; Ali, J
Abstract: Background: Intestinal tuberculosis (IT) poses a real problem of differential diagnosis with Crohn'Disease (CD). Indeed, the distinction between these two pathologies represents a real challenge for clinicians because of their multiple similarities. Based on simple biological, endoscopic and radiological criteria, A new nomogram was developed by Yao He et al. who would differentiate between the two diseases. Objective: To validate externally this new nomogram in a series of patients with IT and CD. Methods: We have collected retrospectively patients diagnosed with CD and IT in our center for a period 11 years old. Patients whose medical file included the data used in the nomogram have been included. The discrimination performance of the nomogram was evaluated by calculating the area under the ROC curve. Results: Of the 76 included patients, 16 had one IT and 60 had one CD. The average age of patients with IT was 44.76 ± 19 years old. The most frequent revealing symptoms were subocclusive syndromes (n = 10) followed by abdominal pain (n = 8). Endoscopic lesions were located in the majority of cases in the ileocecal region (n = 12) and were dominated by the retracted aspect of the cecum (n = 5), transverse colonic ulcerations (n = 4) and valvular stenosis (n = 2). A tumor appearance was noted in two patients.The radiological images of the lungs suggestive of pulmonary tuberculosis were found only in two patients. Intradermal reaction (IDR) to tuberculin was positive in all cases where it was practiced. (n = 14). In ten cases, the diagnosis of ITwas made following bowel resection whose indications were diagnostic uncertainty (n = 4), acute bowel obstruction (n = 4) and suspected CD ileocecal refractory to medical treatment (n = 2). The discrimination of the nomogram analyzed by the ROC curve was 0.956 (95% CI [0.875; 1]). A threshold of 0.5 was associated with a sensitivity of 98.3%; a specificity of 92.8% and a positive and negative predictive value for the diagnosis CD of 98.3 and 92.8 respectively. Conclusion: Although Tunisia is a country of strong endemicity for tuberculosis, intestinal localization seems infrequent and misdiagnosed. The nomogram applied seems to have excellent performance diagnose what could prevent resections intestinal for diagnostic purposes. However, studies multicenter prospective studies remain necessary for a large-scale validation.